Vers une réflexion sur l'agir humain - Bodor, Mária Anna (Verbum – Analecta Neolatina, 2007)
The nature of language and meaning, and interpretation and subjectivity, are issues of increasing concern to a wide range of contemporary disciplines. For philosophers, linguists, social scientists and theologens, the clarifications of such issues has become an urgent and inescapable task. Historical experience is fundamentally the experience of belonging to a tradition that is received from the past. Yet, as Dilthey and Husserl have stressed, experience is essentially expressible, because it can be externalised in signs that need to be understood. In this way it has grown into the culmination of interpretation in an act of appropriation indicates that ontology forms the ultimate horizon of hermeneutics. For Heidegger, understanding is no longer conceived as a way of knowing but as a mode of being (short way), as a fundamental characteristic of our "being-in-the-world". While for Ricoeur (long way), history is in terms of the interaction between two developments: the movement from a regional to a general hermeneutics, and the transition from epistemology to ontology. Consequently, understanding is self-understanding, although the return to the self is not the first, but the final moment in the theory of interpretation. It follows that we shall not only be concerned with reasoned explanation or scientific observation, but shall be watching the emergence of these activities from the mists of a "pre-scientifics" or mythological age (Kerényi). Certainly Pythagoreanism is the most controversial subject in all Greek philosophy, but his vision of an "algorhythmical" cosmos allows us to know the first "locality", by which hermeneutics becomes not only general but fundamental towards a theology of religions.